Responsible Governance and Environmental Disclosure Quality: The Moderating Role of Media Exposure and Media Legitimacy - Marwa Moalla Jamoussi; Anis Jarboui (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research Question- What's the extent voluntary and timely disclosure of environmental information could be explained by the corporate governance? And what's the extent can the media exposure affect the relationship between corporate governance and the quality of disclosure of environmental information on the one hand, and what's the extent can media legitimacy affect this relationship on the other hand? Motivation- The majority of the literature has examined the effect of corporate governance on the voluntary environmental disclosure while neglecting their effect on the timely disclosure of environmental information. Our study seeks to fill this gap by testing the moderating effect of media exposure and media legitimacy on the relationship between responsible governance measured by an index and the quality of environmental disclosure as measured by voluntary disclosure and timely disclosure. This paper is the first comprehensive attempt to analyses the interaction between media exposure and media legitimacy and responsible governance with environmental disclosure quality Idea- This study examines how media exposure and media legitimacy moderate the relationship between the responsible governance and environmental disclosure quality as measured by voluntary and timely disclosure. Data- The data were collected from the reference documents available on the Thomson Reuters Eikon database, including annual reports and sustainability reports. Thus, we collected the data from the Datastream database and from Factiva Database. Tools- This study uses a sample of 81 French non-financial companies listed on the SBF 120 index for the period 2014-2019. Feasible Generalized Least Square (FGLS) regression method is used to estimate the econometric models. Findings- The results obtained show that, for 486 French firm-year observations during the period 2014–2019, show that the media exposure moderates the relationship between the responsible governance and the quality of environmental disclosure as measured by voluntary and timely disclosure. Our results show also that the media legitimacy did not moderate the relationship between the responsible governance and the quality of environmental information. Contribution- The originality of our work consists of the fact that it is one of the first works that deals with the moderator effect of media exposure and media legitimacy on the relationship between responsible governance measured by an index and the quality of disclosure of environmental information measured by voluntary disclosure and timely disclosure. To our knowledge, no empirical study has been done this relationship on the timely disclosure of environmental information in the French context or in other contexts.
Keywords: M41; M42; M48; 650; Media exposure; Media legitimacy; responsible governance; voluntary disclosure; timely disclosure; environmental information